TOKSISITAS GRANULA EKSTRAK BUAH JERUK NIPIS (Citrus aurantifolia L.) TERHADAP MORTALITAS BERUDU (Phyrinoidis aspera) - Renny Ria Fitriani; Dwi Wahyuni; Kamalia Fikri (saintifika, 2017)
Granules extract of clime fruit (Citrus aurantifolia L.) is a biolarvasida in eradicating Aedes aegypti mosquito larvae L. Granules extract of lime fruit (Citrus aurantifolia L.) can kill mosquito larvae because its content of limonoida, tannin, flavonoid, and volatile oil. The compound is lethal to the larvae which will enter the body of the larvae of the Aedes aegypti L. mosquito which disrupts the systems in its body. The purpose of this article is to determine the safety of lime fruit (Citrus aurantifolia L.) extract granules on non-target animals, namely tadpoles. Tadpole has the same habitat with mosquito larvae so it is done safety test of citrus fruit extract granule (Citrus aurantifolia L.). Tadpole is a larval phase in Amphibi that continues to experience morphological development in water. The initial phase of tadpoles growth is a phase of adaptation to its habitat. Individuals who can not adapt well will experience a faster death. The research method used is laboratory experimental. The analysis used is ANOVA. The independent variables in this study were the variety of granules extract concentration of citrus fruit (Citrus aurantifolia L.). Tadpole mortality became the dependent variable in this study. Tadpole mortality is characterized by tadpoles collapsing at the time of administration of granules. The results showed that the lime extract granules (Citrus aurantifolia L.) proved safe.